Muscular Activity Modulation During Post-operative Walking With Hybrid Assistive Limb (HAL) in a Patient With Thoracic Myelopathy Due to Ossification of Posterior Longitudinal Ligament: A Case Report - Kadone, Hideki; Kubota, Shigeki; Abe, Tetsuya; Noguchi, Hiroshi; Miura, Kousei; Koda, Masao; Shimizu, Yukiyo; Hada, Yasushi; Sankai, Yoshiyuki; Suzuki, Kenji; Yamazaki, Masashi (Frontiers in Neurology, 2020)
Disorders of the central nervous system sometimes cause severe sensory motor paralysis accompanied by gait impairment. Recently there are several reports on the effectiveness of robot assisted gait training for patients experiencing these issues. The purpose of this case report is to assess neuro-mechanical effect of a wearable robot suit HAL (Hybrid Assistive Limb) during postoperative gait training in a patient with gait impairment due to compressive myelopathy caused by ossification of posterior longitudinal ligament (OPLL). For this purpose, we compared lower limb muscular activities while the patient was walking with and without the robot through a course of treatment sessions, by (i) gait phase dependent muscle usage analysis, (ii) muscle synergy analysis and (iii) muscle network analysis. Results show (i) enhanced activity of extensor muscles for weight bearing in the initial sessions by using HAL and reduced knee extensor and increased hip extensor activations for achieving larger steps and faster gait in the later sessions, (ii) involvement of greater number of synergies during walking with HAL than without HAL, and (iii) modulated muscle network property during walking with HAL remaining until the next HAL session. The patient’s gait was improved after completing HAL sessions acquiring close to normal joint profile with greater range of joint movement with faster walking speed and larger step length. We discuss that the muscular activity modulation during walking with HAL suggests altered control of the muscles by the central nervous system during postoperative walking. Activity dependent sensorimotor augmentation by HAL is discussed in the context of recovery of gait control by the central nervous system. The relationship between the altered control and the achieved gait recovery requires further investigation.